Comparison Between Diathermy & Stainless Steel Scalpel in Vestibular Incision for Anterior Mandibular Fracture - Farkhunda Mazher, Sonam Nankani, Aftab Ahmed Soomro, Suneel Kumar Punjabi, Anita Kumari, Salman Shams, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare efficacy of the diathermy versus stainless steel scalpel vestibular incision for anterior mandibular fracture. Methodology: Eighty patients having age between 18 to 50 years, irrespective of gender and with mandibular symphysis and parasymphyseal fractures were included and divided into two groups. Group A (diathermy group) and group B (stainless steel scalpel group) included 40 patients each. After selection of patient into either group, the standard protocol of preparation and draping was done and all surgeries were performed under the supervision of supervisor under general anesthesia. The duration of each operation, pain, edema and healing of tissues was noted on the proforma. Results: Male patients were 39 (97.5%) and 37 (92.5%) and female patients were 1 (2.5%) and 3 (7.5%) with mean age of 31.5± 10.7 (18-50) years and34.6± 10.1 (18-50) years in group A (diathermy group) and group B (stainless steel scalpel) respectively. Mean score of pain, edema and healing on Day 7 was significantly higher in Group B as compared to Group A. Conclusion: Diathermy method is more effective in post-operative pain management, edema control (superioinferiorly and mediolaterally) and healing of tissue as vestibular incision for anterior mandibular fracture as compared to stainless steel scalpel method.